(3TQM OjhGf GdeJfHis - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s; (3GdeJfHj , CHh GdWjH,J (B354 (3g` s
(3ChdgG (B:s
(3EPG eG cfJ eZJQHG aLGhQ Hfi MQe Hf bWHI ChOKGQG s
(3BNQgG (B:s
(3EPG gGL eG ai GdbdH ddbdH hMTI aQZJ Edi GSe GdJPcjQ HYOi agPG BNQ eG bGdg ef GdTYQ, Ke NQL ef TjQGR jQjO GdYQGb s
(3hHBNQ UaMGJgG JYbjHIs
(3hChQGbgG eVWQHI GdJQJjHs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
Keywords: (3GdCOHs